INTERFERENCE OF OPERATING SPEED AND PHYSICAL PROPERTIES OF GRANULATED FERTILIZERS WITH THEIR DEPOSITION - Costa,Mariane C. da (2022)
ABSTRACT Uniformity in the deposition of granulated fertilizers in the seed furrow is essential for crop development and productivity. Quantitative (dose and flow) and qualitative factors (segregation and formulation) influence granulated fertilizer distribution throughout its application. This experiment aimed to compare the deposition of two granulated fertilizers with different chemical formulations (04-14-08 and 04-30-10), using the helical overflow metering mechanism at three different operating speeds (4.0, 7.0, and 10.0 km h−1), simulated on an electronic bench. The granulated fertilizers were analyzed for particle size, density, angle of repose, and water content. On the other hand, the deposition data were subjected to descriptive statistics and frequency histograms. The angle of repose and water content did not differ between fertilizers, while the density difference was not significant. The granulated fertilizer 04-30-10 presented the most uniform particle size compared to the granulated fertilizer 04-14-08. The higher particle size uniformity was responsible for a more homogeneous deposition in the seed furrow for the granulated fertilizer 04-30-10 at a speed of 4.0 km h−1, followed by 7.0 km h−1.